Variable order variable stepsize algorithm for solving nonlinear Duffing oscillator - Rasedee, Ahmad Fadly Nurullah; Ishak, Norizarina; Hamzah, Siti Raihana; Ijam, Hazizah Mohd; Suleiman, Mohamed; Ibrahim, Zarina Bibi; Sathar, Mohammad Hasan Abdul; Ramli, Nur Ainna; Kamaruddin, Nur Shuhada (Institute of Physics Publishing, 2017)
Nonlinear phenomena in science and engineering such as a periodically forced oscillator with nonlinear elasticity are often modeled by the Duffing oscillator (Duffing equation). The Duffling oscillator is a type of nonlinear higher order differential equation. In this research, a numerical approximation for solving the Duffing oscillator directly is introduced using a variable order stepsize (VOS) algorithm coupled with a backward difference formulation. By selecting the appropriate restrictions, the VOS algorithm provides a cost efficient computational code without affecting its accuracy. Numerical results have demonstrated the advantages of a variable order stepsize algorithm over conventional methods in terms of total steps and accuracy.